Actual problems of synthetic drug abuse and its legal regulation in Russia - Irina Nailjevna Ainoutdinova, Karina Arturovna Ainoutdinova, (Opción, 2019)
The need for this research was caused by the threatening processes of the global spread of synthetic drug abuse (SDA) and lack of its proper legal regulation in Russia. Based on theoretical, legalistic and comparative approaches, we used both legal and non-legal sources of information to clarify the problem and its conceptual apparatus. We identified that apart from the evident harm caused to teens’ health, the destructive consequences of SDA may expand to a socially dangerous behavior. In conclusion, we make some proposals on revision and extension of the existing sanctions of Article 228 of the Criminal Code of Russia although we recommend maintaining balance while using legal or political instruments of criminalization and decriminalization of acts to ensure effective protection of important social values in accordance with individual freedoms.